Breaking Barriers: Strategies for Overcoming Constraints Faced by Women-led Small-scale Dairy Farm Entrepreneurs in Rural Bangladesh (Indian Journal of Animal Production and Management, 2024)
Rural household-based dairy farming is a  crucial component of meeting the national demand  for nutrition. Despite the significant contributions  women have made to agriculture, particularly in  dairy farming, gender discrimination persists in  access to resources and services, making it  challenging to operate dairy farming effectively. An  exploratory qualitative research project was  conducted in four different areas of Panchgarh  district in Bangladesh to identify the constraints  rural women face in dairy farming and gather their  suggestions for overcoming them. Data was  collected through Focus Group Discussions and  analyzed using NVivo v.14, revealing six recurring  constraints: high input prices, financial challenges,  inadequate marketing facilities, limited training  opportunities, inadequate livestock health services,  and lack of social support. To address these  constraints, women in dairy farming expressed a  desire for effective support in financial, marketing  facilities, training, livestock health treatment, and  community support, which may motivate them to  continue farming and even strengthen their  entrepreneurship. For this, policymakers must  prioritize finding ways to provide work-life balance  for rural dairy women to sustain dairy  entrepreneurship among them. Both government  organizations and non-governmental organizations  must also ensure comprehensive financial,  institutional, and social support systems.  Developing an action plan to address these  suggestions and implementing appropriate actions  is nothing but a demand of time.
Keywords: rural women; dairy farming; Bangladesh; constraints; suggestions